Analysis of Andean Spanish of Aymara-speaking people from Vilquechico district (Puno) - Gonza Huaraya, Mariluz (2020)
In this article, the aim is to analyse the Spanish of the inhabitants of the towns of Poquera, Sacacani and Putira Jutipata, which are located in the district of Vilquechico, within the province of Huancané in the department of Puno. In order to collect the information, an interview was performed, using a semi-structured questionnaire, which also covered the anecdotes, habits, and stories of aforementioned towns, so that the conversation is spontaneous. Then, a corpus of words was created with the collected information and an analysis was carried out to determine what phonologycal and syntactic processes are present in the Andean Spanish of the Aimara-speaking people from Vilquechico district.